2017
DOI: 10.1080/17429145.2017.1385868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a root-colonized dark septate endophyte on the glutathione metabolism in maize plants under cadmium stress

Abstract: A high Cd-tolerant dark septate endophyte (DSE), Exophiala pisciphila, was inoculated into maize (Zea mays L.) roots under Cd stress. The Cd content, enzymes activity and thiol compound content relevant to glutathione (GSH) metabolism in maize leaves were analyzed. The Cd content in maize shoots increased with increasing Cd stress, but the DSE significantly reduced the Cd content at the 40 mg/ kg Cd treatment. Cd stress increased the enzyme activity of glutathione reductase (GR), glutathione S-transferase (GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 60 publications
8
20
1
Order By: Relevance
“…Research has shown that endophytic fungi inhabit most plant roots in habitats polluted by Cd (Li et al, 2012;Yu et al, 2019). The significant effects of the endophytic fungi on plant growth and Cd tolerance have also been demonstrated (He et al, 2017;Zhan et al, 2017). In the present study, the hyphae and the microsclerotial structures of the DSEs were observed in all inoculated M. sativa and A. mongolicus roots after harvesting.…”
Section: Effects Of Dse Inoculation On Non-host Plantssupporting
confidence: 72%
“…Research has shown that endophytic fungi inhabit most plant roots in habitats polluted by Cd (Li et al, 2012;Yu et al, 2019). The significant effects of the endophytic fungi on plant growth and Cd tolerance have also been demonstrated (He et al, 2017;Zhan et al, 2017). In the present study, the hyphae and the microsclerotial structures of the DSEs were observed in all inoculated M. sativa and A. mongolicus roots after harvesting.…”
Section: Effects Of Dse Inoculation On Non-host Plantssupporting
confidence: 72%
“…In general, the Cd concentration was relatively less in the aboveground and belowground tissues of E+ plants in most of the treatments ( Table 1 ). This finding was similar to the results of the previous studies that observed lower Cd in inoculated plants than non-inoculated plants ( Wang et al, 2016 ; He et al, 2017 ; Zhan et al, 2017 ; Zhu et al, 2018 ; Shahid et al, 2019 ). However, in this study, the difference was non-significant ( p > 0.05) in most of the tested conditions ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, GSH content of E+ plants was more than that of E− plants (Figure 3), which indicates the counteractive mechanism developed by inoculated endophyte to check oxidative stress due to Cd. The results were consistent with previous studies, which observed endophytic inoculation may improve the host plant growth and tolerance to Cd stress through GSH regulation in different host plants (Khan et al, 2015;Wang et al, 2016;He et al, 2017;Zhan et al, 2017;Zhang et al, 2019).…”
Section: Physiological and Biochemical Changessupporting
confidence: 93%
“…In our study, BS inoculation increased the GSH content of plants under NaCl stress, and PC inoculation increased the GSH content in plants under 0.1% NaCl; however, an increase in GSH content in the AC-inoculated plants was detected only under 0.2% and 0.3% NaCl. Similar results in which DSE could activate GSH metabolism in Zea mays under heavy metal stress have been reported [65]. These results indicated that, by regulating the accumulation of antioxidants and the Na + :K + balance, DSE can alleviate the adverse effects of NaCl stress on plants.…”
Section: Discussionsupporting
confidence: 86%